Interface force and electrochemical synergistic failure simulation method of carbon fiber structure battery
Patent Information
- Application Number
- CN202611393347.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]然而,在低速冲击荷载的工况下,由于低速冲击引发的惯性效应、应力波传播和局部化应力集中,极易导致碳纤维电极与电解质界面发生脱粘或分层的动态演化过程,而上述现有技术由于仅考虑了模拟结构电池界面在充放电过程中因锂离子浓度变化而产生的膨胀/收缩过程,对于低速冲击工况下的电池界面发生的脱粘或分层的力学演化是如何阻碍电荷转移反应的动态过程,上述现有技术无法进行模拟,导致上述现有技术在低速冲击荷载的动态工况下无法适用
当低速冲击荷载导致碳纤维电极与固-液双连续相电解质界面发生脱粘或分层时,碳纤维电极表面与电解质之间的固液物理接触被破坏,脱粘或分层区域不再具备电荷转移能力,本发明创新地将损伤变量通过有效接触面积分数形式引入Butler-Volmer电极动力学方程以构建损伤耦合控制方程,基于损伤耦合控制方程,随着作用于电池界面的低速冲击荷载的逐渐增大,界面损伤变量增大,有效接触面积分数相应减小,使得脱粘或分层区域面积变大,脱粘或分层区域面积变大导致实际参与界面电荷转移反应的活性位点变少,从而阻碍了电池界面的电荷转移反应,通过损伤耦合控制方程描述的上述演化过程,显示表征了低速冲击工况下的电池界面发生的脱粘或分层的演化阻碍电荷转移反应的动态过程,实现了界面力学损伤的演化过程与电化学性能的衰减过程的有效耦合。
Smart Images

Figure CN123013210A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of structural battery simulation technology, and in particular to a simulation method for the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structural batteries. Background Technology
[0002] Structural batteries are a type of multifunctional composite material that combines structural support with electrochemical energy storage. Using carbon fiber as the active electrode material, significant weight and volume savings can be achieved at the system level. The latest generation of carbon fiber structural batteries typically consists of a carbon fiber composite cathode, a solid-liquid dual-phase electrolyte, and a carbon fiber anode. Carbon fiber simultaneously serves as both a mechanical reinforcement and an electrochemical active material. In practical applications, especially in electric vehicles, structural batteries inevitably encounter low-speed impacts (typically in the 4J-14J range) such as stone strikes and tool drops. These impacts can lead to debonding or delamination at the carbon fiber electrode-electrolyte interface, resulting in mechanochemical synergistic failure—the coupling effect of mechanical damage and electrochemical performance degradation.
[0003] In the prior art, a multi-physics coupling simulation method at the microscale of structural energy storage integrated composite materials is provided to evaluate the synergistic failure of force and electrochemistry. It mainly simulates the synergistic failure between interfacial force and electrochemistry of structural batteries by simulating the expansion / contraction of the battery interface due to changes in lithium ion concentration through the intercalation strain effect of the structural battery during static charging and discharging.
[0004] However, under low-speed impact load conditions, the inertial effect, stress wave propagation, and localized stress concentration caused by the low-speed impact can easily lead to the dynamic evolution process of debonding or delamination at the interface between the carbon fiber electrode and the electrolyte. The aforementioned existing technologies only consider the expansion / contraction process of the battery interface due to changes in lithium ion concentration during charging and discharging. They cannot simulate how the mechanical evolution of debonding or delamination at the battery interface under low-speed impact conditions hinders the dynamic process of charge transfer reaction. As a result, the aforementioned existing technologies are not applicable under the dynamic conditions of low-speed impact load. Summary of the Invention
[0005] Therefore, it is necessary to provide a simulation method for the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structure batteries to address the aforementioned technical problems.
[0006] The present invention adopts the following technical solution: This invention provides a simulation method for the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structure batteries, comprising: A three-dimensional geometric model of a carbon fiber structure battery is constructed, and an interface domain is constructed between each carbon fiber electrode and the electrolyte. A dynamic load simulating low-speed impact is applied to the three-dimensional geometric model, and the interface force parameters of the interface domain under low-speed impact load are obtained. Based on the interface stress parameters, an interface cohesive damage model based on the bilinear traction-separation law is used to determine the damage variables used to characterize the degree of interface damage in carbon fiber structure batteries; wherein, the interface cohesive damage model is used to describe the evolution of interface debonding or delamination under low-speed impact load. Based on the damage variables of carbon fiber structure batteries, an effective contact area fraction is determined to characterize the tensile or compressive state of the carbon fiber structure battery interface under low-speed impact loading. This effective contact area fraction is then introduced into the Butler-Volmer electrode kinetic equation to construct a damage coupling control equation between interfacial forces and electrochemistry in the carbon fiber structure battery. The damage variables are inversely proportional to the effective contact area fraction. This damage coupling control equation is used to simulate the dynamic process by which the evolution of interfacial debonding or delamination hinders the charge transfer reaction in the carbon fiber structure battery. The damage coupling control equation was solved by finite element simulation, and the simulation results of the interfacial force and electrochemical synergistic failure of carbon fiber structure battery under low-speed impact were obtained.
[0007] Preferably, a three-dimensional geometric model of the carbon fiber structure battery is constructed, and an interface domain is constructed between each carbon fiber electrode and the electrolyte, specifically including: Obtain the characteristic dimension parameters of each part of the carbon fiber structure battery; Based on the aforementioned characteristic size parameters, a three-dimensional geometric model is constructed, comprising a carbon fiber negative electrode, a solid-liquid dual-continuous phase electrolyte, a membrane, and a carbon fiber positive electrode. An interface domain is constructed between the carbon fiber negative electrode and the solid-liquid dual-continuous phase electrolyte, and between the carbon fiber positive electrode and the solid-liquid dual-continuous phase electrolyte.
[0008] Preferably, after constructing the interface domain between each carbon fiber electrode and the electrolyte, the method further includes: setting material parameters for the interface domain, specifically including: An anisotropic force-electrochemical coupling constitutive relation based on the Helmholtz free energy function is assigned to carbon fiber anode and carbon fiber cathode; wherein the Helmholtz free energy function is composed of elastic strain energy, lithium-ion mixing entropy term and lithium-ion interaction energy term; The solid-liquid bicontinuous phase electrolyte is made of resin-based material and is endowed with elastic and ion-conducting properties, as well as isotropic elastic properties for the diaphragm.
[0009] Preferably, the interface force parameters of the interface domain under low-speed impact load include: interface traction force, interface strength, interface stiffness tensor, and interface separation displacement.
[0010] Preferably, based on the interfacial stress parameters, an interfacial cohesive damage model based on the bilinear traction-separation law is used to determine the damage variables used to characterize the degree of interfacial damage in carbon fiber structure batteries, specifically including: When the sum of the ratios of the normal and tangential components of the interfacial traction force to their respective interfacial strength components is 1, the stress parameters of the carbon fiber structure battery interface are determined as the damage initiation state of the carbon fiber structure battery interface. Under the initial damage state of the carbon fiber structure battery interface, the initiation and evolution process of debonding or delamination of the carbon fiber structure battery interface under a preset impact load is simulated by the interface cohesive damage model. During the simulation, the damage variables of the carbon fiber structure battery interface are determined based on the interface separation displacement.
[0011] Preferably, based on the damage variables of the carbon fiber structure battery, the effective contact area fraction used to characterize the tensile or compressive state of the carbon fiber structure battery interface under low-speed impact load is determined, specifically including: When the interface is in a stretched state, the difference between the effective contact area fraction of 1 and the damage variable is determined based on the damage variable. When the interface is in a compressed state, the effective contact area fraction is determined to be the larger of the difference between the damage variable and the preset minimum contact fraction.
[0012] Preferably, the effective contact area fraction is incorporated into the Butler-Volmer electrode kinetics equation to construct the damage coupling control equation between interfacial forces and electrochemistry in the carbon fiber structure battery, specifically including: Introducing the effective contact area fraction as a correction factor into the Butler-Volmer electrode kinetics equation yields the coupled control equations for the mechanical, electrochemical, and damage aspects of the carbon fiber structure battery interface, expressed as: ; In the formula, This represents the interfacial lithium-ion flux. For exchange current density, It is Faraday's constant. For the overpotential term, 、 Charge transfer coefficient; effective contact area fraction With damage variables The relationship is When the interface is completely damaged This indicates that the charge transfer reaction has terminated; The Butler-Volmer electrode kinetics equations also incorporate a mechanical contribution term into the overpotential term. This term describes the evolution of the concentration gradient stress reaction on interface damage caused by lithium ion insertion or extraction at the carbon fiber battery interface under low-velocity impact loading. The expression is as follows: ; In the formula, The electrode potential is... The potential of the electrolyte. To balance the electric potential, This represents the partial molar volume of lithium ions. For hydrostatic stress, Contribution to mechanics.
[0013] Preferably, the damage coupling control equation is solved by finite element simulation, specifically including: Low-speed impact dynamic load boundary conditions are set for the three-dimensional geometric model of the carbon fiber structure battery. The boundary conditions include the mass, initial velocity and geometry of the impacting object. Set up contact pairs between the impactor and the surface of the carbon fiber structure battery, and apply fixed constraints on both sides of the carbon fiber structure battery. Considering the inertial effect, stress wave propagation, and strain rate effect experienced by the interface of a carbon fiber structure battery under low-speed impact dynamic load, the damage coupling control equation is solved by finite element method using explicit dynamic analysis, and the simulation results of the interface force and electrochemical synergistic failure of the carbon fiber structure battery under low-speed impact are output.
[0014] Preferably, the simulation results of the synergistic failure of the interfacial force and electrochemical properties of the carbon fiber structure battery under low-speed impact include: damage evolution cloud map of the carbon fiber structure battery interface during low-speed impact, current density distribution map after impact, potential change curve and lithium ion concentration distribution map.
[0015] This invention provides a simulation device for the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structure batteries, comprising: A 3D model building module is used to construct a 3D geometric model of a carbon fiber structure battery and to build an interface domain between each carbon fiber electrode and the electrolyte; to apply a dynamic load simulating low-speed impact to the 3D geometric model and to obtain the interface force parameters of the interface domain under low-speed impact load. The interface evolution simulation module is used to determine the damage variables used to characterize the degree of interface damage of carbon fiber structure batteries based on the interface stress parameters and the interface cohesive damage model based on the bilinear traction-separation law; wherein, the interface cohesive damage model is used to describe the evolution of interface debonding or delamination under low-speed impact load. A coupling equation construction module is used to determine the effective contact area fraction, which characterizes the tensile or compressive state of the carbon fiber structure battery interface under low-speed impact loading, based on the damage variables of the carbon fiber structure battery. This effective contact area fraction is then introduced into the Butler-Volmer electrode kinetics equation to construct a damage coupling control equation between the interfacial forces and electrochemistry of the carbon fiber structure battery. The damage variables are inversely proportional to the effective contact area fraction. This damage coupling control equation is used to simulate the dynamic process by which the evolution of interfacial debonding or delamination hinders the charge transfer reaction of the carbon fiber structure battery. The interface evaluation simulation module is used to solve the damage coupling control equation using finite element simulation, and obtain simulation results of the interfacial force and electrochemical synergistic failure of carbon fiber structure batteries under low-speed impact.
[0016] This invention provides a computer-readable storage medium storing a computer program that, when executed by a processor, implements the aforementioned simulation method for the interfacial force and electrochemical synergistic failure of a carbon fiber structure battery.
[0017] The present invention provides a computer device, including a memory, a processor, and a computer program stored in the memory and executable on the processor. When the processor executes the program, it implements the above-mentioned simulation method for the interfacial force and electrochemical synergistic failure of a carbon fiber structure battery.
[0018] The above-mentioned at least one technical solution adopted in this invention can achieve the following beneficial effects: When low-velocity impact loads cause debonding or delamination at the interface between the carbon fiber electrode and the solid-liquid bicontinuous electrolyte, the solid-liquid physical contact between the carbon fiber electrode surface and the electrolyte is disrupted, and the debonded or delaminated region no longer possesses charge transfer capability. This invention innovatively introduces the damage variable into the Butler-Volmer electrode kinetic equation in the form of an effective contact area fraction to construct a damage coupling control equation. Based on the damage coupling control equation, as the low-velocity impact load acting on the battery interface gradually increases, the interface damage variable increases, and the effective contact area fraction decreases accordingly, resulting in a larger area of the debonded or delaminated region. The larger area of the debonded or delaminated region leads to fewer active sites actually participating in the interface charge transfer reaction, thereby hindering the charge transfer reaction at the battery interface. The above evolution process described by the damage coupling control equation shows the dynamic process of the evolution of debonding or delamination at the battery interface under low-velocity impact conditions hindering the charge transfer reaction, realizing the effective coupling of the evolution process of interface mechanical damage and the decay process of electrochemical performance. Attached Figure Description
[0019] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings:
[0020] Figure 1 A flowchart illustrating the simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery provided by this invention. Figure 2 A schematic diagram of the full cell structure of a carbon fiber structure battery, which is provided by the present invention for simulating the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery. Figure 3 A schematic diagram of the traction-separation law of the interfacial cohesive damage model in a simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery provided by this invention. Figure 4 This is a schematic diagram of the simulation device for a simulation method of interfacial force and electrochemical synergistic failure of a carbon fiber structure battery provided by the present invention. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this application will be clearly and completely described below in conjunction with specific embodiments and corresponding drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments in the specification without creative effort are within the scope of protection of this application.
[0022] The technical solutions provided by the various embodiments of this application are described in detail below with reference to the accompanying drawings.
[0023] Figure 1 This is a schematic diagram of the simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery according to the present invention, which specifically includes the following steps: S101: Construct a three-dimensional geometric model of the carbon fiber structure battery and build an interface domain between each carbon fiber electrode and the electrolyte; apply a dynamic load simulating low-speed impact to the three-dimensional geometric model and obtain the interface force parameters of the interface domain under the low-speed impact load.
[0024] Specifically, constructing interface domains between each carbon fiber electrode and the electrolyte includes: obtaining characteristic size parameters of each part of the carbon fiber structure battery; constructing a three-dimensional geometric model containing a carbon fiber negative electrode, a solid-liquid dual-continuous phase electrolyte, a separator, and a carbon fiber positive electrode based on the characteristic size parameters; and constructing interface domains between the carbon fiber negative electrode and the solid-liquid dual-continuous phase electrolyte, and between the carbon fiber positive electrode and the solid-liquid dual-continuous phase electrolyte.
[0025] After constructing the interface domain between each carbon fiber electrode and the electrolyte, the method further includes setting material parameters for the interface domain, specifically including: assigning anisotropic force-electrochemical coupling constitutive relations based on the Helmholtz free energy function to the carbon fiber negative electrode and the carbon fiber positive electrode; wherein the Helmholtz free energy function is composed of elastic strain energy, lithium-ion mixing entropy term and lithium-ion interaction energy term; the solid-liquid dual continuous phase electrolyte adopts a resin-based material and is endowed with elastic and ion conduction properties, and the membrane is endowed with isotropic elastic properties.
[0026] Among them, the interface force parameters of the interface domain include: interface traction force, interface strength, interface stiffness tensor, and interface separation displacement.
[0027] S102: Based on the interface stress parameters, the interface cohesive damage model based on the bilinear traction-separation law is used to determine the damage variables used to characterize the degree of interface damage of carbon fiber structure battery; wherein, the interface cohesive damage model is used to describe the evolution of interface debonding or delamination under low-speed impact load.
[0028] Optionally, based on the interface stress parameters, an interface cohesive damage model based on the bilinear traction-separation law is used to determine the damage variables used to characterize the degree of interface damage of the carbon fiber structure battery. Specifically, when the sum of the ratios of the normal and tangential components of the interface traction force to their respective interface strength components is 1, the stress parameters of the carbon fiber structure battery interface are determined as the damage initiation state of the carbon fiber structure battery interface. Under the damage initiation state of the carbon fiber structure battery interface, the interface cohesive damage model is used to simulate the initiation and evolution process of debonding or delamination of the carbon fiber structure battery interface under a preset impact load, and the damage variables of the carbon fiber structure battery interface are determined based on the interface separation displacement during the simulation process.
[0029] S103: Based on the damage variables of the carbon fiber structure battery, determine the effective contact area fraction used to characterize the tensile or compressive state of the carbon fiber structure battery interface under low-speed impact load; introduce the effective contact area fraction into the Butler-Volmer electrode kinetic equation to construct the damage coupling control equation between interfacial force and electrochemistry of the carbon fiber structure battery; wherein, the damage variable is inversely proportional to the effective contact area fraction; the damage coupling control equation is used to simulate the dynamic process by which the evolution of interfacial debonding or delamination hinders the charge transfer reaction of the carbon fiber structure battery.
[0030] Optionally, based on the damage variables of the carbon fiber structure battery, an effective contact area fraction is determined to characterize the tensile or compressive state of the carbon fiber structure battery interface under low-speed impact load. Specifically, this includes: when the interface is in a tensile state, determining the effective contact area fraction as the difference between 1 and the damage variable based on the damage variable; and when the interface is in a compressive state, determining the larger value between the effective contact area fraction as 1 and the damage variable and a preset minimum contact fraction.
[0031] Optionally, the effective contact area fraction is incorporated into the Butler-Volmer electrode kinetics equation to construct the damage coupling control equation between interfacial forces and electrochemistry in the carbon fiber structure battery, specifically including: Introducing the effective contact area fraction as a correction factor into the Butler-Volmer electrode kinetics equation yields the coupled control equations for the mechanical, electrochemical, and damage aspects of the carbon fiber structure battery interface, expressed as: ; In the formula, This represents the interfacial lithium-ion flux. For exchange current density, It is Faraday's constant. For the overpotential term, 、 Charge transfer coefficient; effective contact area fraction With damage variables The relationship is When the interface is completely damaged This indicates that the charge transfer reaction has terminated; The Butler-Volmer electrode kinetics equations also incorporate a mechanical contribution term into the overpotential term. This term describes the evolution of the concentration gradient stress reaction on interface damage caused by lithium ion insertion or extraction at the carbon fiber battery interface under low-velocity impact loading. The expression is as follows: ; In the formula, The electrode potential is... The potential of the electrolyte. To balance the electric potential, This represents the partial molar volume of lithium ions. For hydrostatic stress, Contribution to mechanics.
[0032] S104: The damage coupling control equation was solved by finite element simulation to obtain the simulation results of the interfacial force and electrochemical synergistic failure of carbon fiber structure battery under low-speed impact.
[0033] Optionally, the damage coupling control equation is solved using the finite element method, specifically including: setting low-speed impact dynamic load boundary conditions for the three-dimensional geometric model of the carbon fiber structure battery, wherein the boundary conditions include the mass, initial velocity, and geometry of the impactor; setting contact pairs between the impactor and the surface of the carbon fiber structure battery, and applying fixed constraints on both sides of the carbon fiber structure battery; considering the inertial effect, stress wave propagation, and strain rate effect experienced by the interface of the carbon fiber structure battery under low-speed impact dynamic load, the damage coupling control equation is solved using explicit dynamic analysis using the finite element method, and the simulation results of the interface force and electrochemical synergistic failure of the carbon fiber structure battery under low-speed impact are output.
[0034] Optionally, the simulation results of the synergistic failure of the interfacial force and electrochemical properties of the carbon fiber structure battery under low-speed impact include: damage evolution cloud map of the carbon fiber structure battery interface during low-speed impact, current density distribution map after impact, potential change curve and lithium ion concentration distribution map.
[0035] To verify the effectiveness of the present invention, the specific implementation steps and technical details of the present invention are provided below.
[0036] Step 1: Obtain the feature size parameters of each part of the target structure battery.
[0037] In this embodiment, the structure of the carbon fiber structure battery full cell is as follows: Figure 2 As shown, it includes: a carbon fiber composite positive electrode (composed of a carbon fiber fabric current collector and a positive electrode active layer), a resin-based solid-liquid dual-continuous phase electrolyte, a separator, and a carbon fiber negative electrode (composed of a carbon fiber fabric current collector and a negative electrode active layer). The positive electrode active layer can be made of materials such as lithium iron phosphate (LFP) or lithium nickel cobalt manganese oxide (NMC), while the negative electrode active layer can be made of graphite or carbon-based materials. The resin-based solid-liquid dual-continuous phase electrolyte is an ion-conducting polymer system with a dual-continuous phase structure, composed of a polymer matrix (such as E51 epoxy resin) and a liquid electrolyte (such as LiTFSI / LiBOB salt in EC / PC).
[0038] The characteristic dimension parameters of each part of the target structure battery were obtained in the following way: A sample of the target structure battery was fabricated, and the cross-section of the sample was photographed using a super depth-of-field microscope. Image analysis software was used to analyze the cross-sectional images. Based on the scaling ratio of the cross-sectional images to the target battery structure, measurement tools were used to determine the characteristic dimensional parameters of each part, including: the shape and size of the positive and negative electrode active layers, the cross-sectional shape and yarn height of the carbon fiber current collector, and the cross-sectional shape and yarn height of the separator.
[0039] Step 2: Construct a three-dimensional geometric model and assign material properties.
[0040] Based on the feature size parameters obtained in step 1, a three-dimensional geometric model containing the carbon fiber negative electrode, resin-based electrolyte, separator, and carbon fiber positive electrode is constructed in modeling software such as TexGen or COMSOL Multiphysics. Specifically, interface domains are constructed between the carbon fiber negative electrode and the resin-based electrolyte, and between the carbon fiber positive electrode and the resin-based electrolyte, with a thickness of 0.1-1 μm, for subsequent introduction of interface damage models.
[0041] Assign material properties to each domain: (1) Carbon fiber negative electrode and carbon fiber positive electrode An anisotropic force-electrochemical coupling constitutive relation is assigned based on the Helmholtz free energy. The Helmholtz free energy function of carbon fiber is expressed as:
[0042] ; in, For strain tensor, Lithium ion concentration (mol / m³) The chemical expansion tensor (m³ / mol) includes the longitudinal expansion coefficient. and lateral expansion coefficient , The reference concentration for the stress-free state. Let Pa be the concentration-dependent anisotropic stiffness tensor. The maximum lithium-ion concentration (mol / m³) is given. Reference chemical potential (J / mol) It is the ideal gas constant (8.314 J·mol⁻¹·K⁻¹). Temperature (K) The interaction parameter is (J·m³ / mol²).
[0043] The stress constitutive relation derived from this is: (1); The expression for chemical potential is: (2); The first term in equation (2) This directly reflects the influence of stress on chemical potential, constituting the core mechanism of force-electric coupling.
[0044] Neglecting the slight effect of concentration on stiffness (the last term), we obtain a chemical potential expression suitable for engineering applications: (3); The corresponding equilibrium electrode potential is: (4); in, is the Faraday constant (96485 C·mol⁻¹). The last term in equation (4) This is the contribution of stress to the potential, and it is a measurable manifestation of force-electric coupling.
[0045] The lithium-ion flux in carbon fibers is driven by a chemical potential gradient: (5); in, For mobility, and diffusion coefficient The relationship is .
[0046] (2) Resin-based solid-liquid bicontinuous phase electrolyte (6); in, For the isotropic stiffness tensor, and These represent the lithium ion and anion concentrations, respectively. and For reference chemical potential, For reference concentration, Where is the dielectric constant. It represents the electric potential.
[0047] Ion flux is described by the Nernst-Planck equation: (7); (8); in, and The values represent the mobility of lithium ions and anions, respectively.
[0048] Ionic conductivity and migration number It is correlated with ion mobility through the following relationship: (9); (3) Diaphragm Membranes (such as fiberglass woven fabric) impart isotropic elastic properties and modify ion transport parameters according to their porosity and tortuosity. (10); in, For the membrane porosity, This is the tortuosity factor.
[0049] Step 3: Introduce the interface cohesive damage model.
[0050] An interfacial cohesive damage model is introduced in the interfacial domain between the carbon fiber electrode and the resin-based solid-liquid bicontinuous electrolyte to describe the initiation and evolution of interfacial debonding or delamination under low-velocity impact loading. This embodiment employs a bilinear traction-separation rule, and its constitutive relation can be expressed as:
[0051] (11); in, For interface traction force, For interface separation displacement, For the interface stiffness tensor, As a damage variable, For Macaulay brackets (contact stiffness recovery only upon indentation). It is the normal unit vector.
[0052] The damage initiation criterion adopts the second nominal stress criterion: (12); in, 、 、 These are the normal and two tangential traction force components, respectively. 、 、 This represents the corresponding interface strength.
[0053] Damage evolution is driven by the effective separation displacement of the interface generated by impact deformation, and the damage variable is... The model outputs physical quantities, and the calculation formulas are as follows: (13); in, The effective displacement at the onset of damage. From fracture energy and effective strength Decide, This represents the maximum effective displacement during the loading process. Defined as:
[0054] (14); in, For normal separation displacement, and This represents the tangential separation displacement.
[0055] Step 4: Construct the system of governing equations for the multi-field coupling of mechanics, electrochemistry, and damage. In the dynamic response process of low-velocity impact, the damage variable D output in step S3 is expressed as the effective contact area fraction. This is incorporated into the Butler-Volmer electrochemical kinetic equations for the interface. When low-velocity impacts lead to interfacial debonding, κ decreases with increasing D, directly weakening the interfacial charge transfer reaction rate. This allows for real-time and quantitative simulation of the current density redistribution and potential drop phenomena at the moment of impact. Simultaneously, a mechanical contribution term is introduced into the overpotential driving the electrochemical reaction, enabling the concentration gradient stress generated by lithium-ion insertion / extraction under low-velocity impacts to react on the evolution of interfacial damage, forming a complete two-way coupled closed loop.
[0056] This mechanism enables, for the first time, real-time co-simulation of interfacial mechanical damage and electrochemical performance degradation under the complex dynamic condition of low-speed impact, which includes inertial effects and stress wave propagation.
[0057] The damage variable output from step 3 Introduced into electrochemical boundary conditions to correct charge transfer reactions at the interface caused by contact separation.
[0058] First, define the effective area fraction. : (15); in This is the minimum contact fraction (considering rough surface contact, it can be taken as 0.1-0.3).
[0059] The lithium-ion flux at a perfect interface is described by the Butler-Volmer equation: (16); in, The exchange current density (A / m²) depends on the lithium-ion concentration on both sides of the interface: (17); The reaction rate constant is... The lithium concentration at the electrode surface. This represents the lithium concentration in the electrolyte. 、 The charge transfer coefficient (usually taken as...) = =0.5).
[0060] overpotential Includes mechanical contributions: (18); in, The electrode potential is... The potential of the electrolyte. The equilibrium potential is given by equation (4). This represents the partial molar volume of lithium ions. For hydrostatic stress, the last term Contribution to mechanics.
[0061] effective area fraction Introducing the BV equation, the corrected interfacial lithium-ion flux is: (19); The corresponding interface current density is: (20); The double-layer capacitance at the interface is also proportional to the effective area: (twenty one); The complete set of force-electricity-damage coupling control equations includes: Mechanical field equations (considering inertial effects): (twenty two); (twenty three); (twenty four); Electrochemical field equations (mass conservation): (25); Charge conservation: (26); in, is the diffusion conductivity.
[0062] Interface coupling conditions: (27); (28); (29); Step 5: Apply low-speed impact dynamic load and perform finite element solution.
[0063] Apply dynamic load boundary conditions to simulate low-speed impact: Define the mass m, initial velocity v0, and geometry of the impactor (a hemispherical impact head with a diameter of 16 mm is used in this embodiment), set the contact pairs between the impactor and the surface of the structural battery, and apply fixed constraints on both sides of the structural battery.
[0064] Considering dynamic effects, the equation of motion is shown in equation (22). This embodiment uses explicit dynamic analysis (such as the central difference method) for finite element solution to account for inertial effects, stress wave propagation, and strain rate effects. The time integral format for explicit dynamics is:
[0065] (30); 31); Where Δt is the time step, and the CFL stability condition must be satisfied: (32); in, For the smallest unit size, For material wave velocity, It is Young's modulus.
[0066] During the solution process, the force-electricity-damage coupling control equations are solved using an alternating iterative method. Within each time step: Fixed Concentration Field Solve the mechanical equations (21)-(23) to obtain the displacement field. and damage field ; Update effective area fraction = 1 − (Stretching / Shearing); fixed and Solve the electrochemical equations (24)-(25) to obtain the concentration field. and electric potential field ; Check convergence: , ; If it doesn't subside, update. k←k+ 1. Continue iterating.
[0067] Step 6: Output simulation results.
[0068] After the solution is completed, the following simulation results are output: Interface damage evolution cloud map shows the initiation and expansion of interface debonding regions during impact; The current density distribution map after the impact reveals the redistribution of current density caused by the damage; The potential change curve shows the voltage drop and recovery behavior at the moment of impact and afterwards; The lithium ion concentration distribution map shows the accumulation or depletion of lithium ions in the damaged area.
[0069] Model validation and parameter calibration This embodiment verifies the accuracy of the proposed method by comparing experimental data and simulation results, and performs parameter calibration.
[0070] The experimental sample was a carbon fiber structure battery full cell prepared according to the structure described in Example 1. The positive electrode was made of LFP-coated carbon fiber fabric, the negative electrode was made of T800 carbon fiber, and the electrolyte was an EBADMA-based resin-based solid-liquid dual-phase battery electrolyte (SBE). Low-speed impact tests were conducted on an Instron 9350 drop hammer impact testing machine with impact energies of 4J, 8J, and 14J. The impact head diameter was 16mm and the mass was 5.618kg. During the impact, the open-circuit potential change of the battery was monitored in real time using a potentiostat.
[0071] The above experiment was simulated using the simulation method of this invention, and the key parameters were calibrated using the least squares method: (33); in, and These are the potential values from simulation and experiment, respectively. The set of parameters to be calibrated includes interface strength. Interfacial fracture energy Longitudinal expansion coefficient of carbon fiber Exchange current density wait.
[0072] Sensitivity Analysis and Engineering Applications: This embodiment uses the proposed method to perform sensitivity analysis and identify key factors affecting the impact resistance performance of the structural battery.
[0073] The sensitivity of each input parameter to the output response (such as peak damage area and maximum voltage drop) is calculated by individually perturbing each parameter (with a perturbation amplitude of ±10%). Sensitivity coefficient. Defined as:
[0074] (34); Based on the results of sensitivity analysis, the following suggestions are made for optimizing the impact resistance of the battery structure: in, R To output the response, For the first There are 10 input parameters. The sensitivity analysis results are shown in Table 1.
[0075] Table 1. Results of parameter sensitivity analysis Interface strength 2.34 1.87 Interfacial fracture energy 1.92 1.56 Longitudinal expansion coefficient of carbon fiber 0.67 2.13 Exchange current density 0.12 1.45 Electrolyte conductivity 0.08 0.93 Impact energy 1.76 1.82 The analysis results show that: Interface strength and fracture energy The impact on the surface damage area after impact is the most significant factor, and it is a key mechanical parameter that determines the impact resistance of the structural battery. Longitudinal expansion coefficient of carbon fiber It is most sensitive to voltage drop, which reflects the dominant role of the force-electric coupling strength in the degradation of electrochemical performance; Exchange current density and electrolyte conductivity It primarily affects the electrochemical recovery behavior after damage.
[0076] Interface modification strategy: Improve the interfacial strength between carbon fiber electrodes and resin-based solid-liquid dual-phase electrolytes through plasma treatment, surface grafting, or the introduction of flexible interfacial layers. It is recommended to increase the normal interfacial strength to above 30 MPa and the tangential interfacial strength to above 20 MPa, while maintaining a fracture energy of not less than 200 J / m².
[0077] Carbon fiber selection and pretreatment: Select carbon fibers with a moderate longitudinal expansion coefficient (0.004-0.006) and adjust the initial lithium concentration to the optimal range (approximately 6-8% of the maximum concentration) through pre-lithiation treatment to balance the force-electric coupling strength and structural stability.
[0078] Electrolyte formulation optimization: The ionic conductivity of the resin-based solid-liquid bicontinuous phase electrolyte was increased to above 0.2 S / m, and the bicontinuous phase structure was optimized to enhance ion transport capacity and accelerate electrochemical recovery after damage. The migration number was optimized to around 0.4 by adjusting the ratio of polymer matrix to liquid electrolyte.
[0079] Layer structure optimization: Add gradient stiffness transition layers (such as resin or fiber layers with different moduli) around the cell to alleviate stress concentration at the interface; use braided structures or Z-pin reinforcement technology to improve interlayer fracture toughness.
[0080] Damage monitoring and early warning: Based on the key damage areas identified by simulation, strain sensors are pre-embedded in the structural battery or the piezochemical effect of carbon fiber itself is used to achieve real-time monitoring and early warning of impact damage.
[0081] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this invention.
[0082] The above describes a simulation method for the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structure batteries, provided by one or more embodiments of the present invention. Based on the same idea, the present invention also provides a corresponding simulation device for evaluating the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structure batteries under low-velocity impact, such as... Figure 4 As shown.
[0083] Figure 4This invention provides a schematic diagram of a simulation device for evaluating the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structure batteries under low-velocity impact. The device includes: The three-dimensional model building module 401 is used to construct the interface domain of the three-dimensional geometric model of the carbon fiber structure battery; and to obtain the interface force parameters of the interface domain when subjected to low-speed impact load. The interface evolution simulation module 402 is used to determine the damage variables used to characterize the degree of interface damage of carbon fiber structure batteries based on the interface stress parameters and the interface cohesive damage model based on the bilinear traction-separation law. The coupling equation construction module 403 is used to determine the effective contact area fraction, which characterizes the tensile or compressive state of the carbon fiber structure battery interface under low-speed impact load, based on the damage variables of the carbon fiber structure battery; the effective contact area fraction is introduced into the Butler-Volmer electrode kinetic equation to construct the damage coupling control equation between the interfacial force and electrochemistry of the carbon fiber structure battery; wherein the damage variable is inversely proportional to the effective contact area fraction. The interface evaluation simulation module 404 is used to solve the damage coupling control equation using finite element method to obtain the simulation results of the interface force and electrochemical synergistic failure of carbon fiber structure battery under low-speed impact.
[0084] Specific limitations regarding the simulation device for evaluating the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structure batteries under low-velocity impact can be found in the above description of the simulation method for the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structure batteries, and will not be repeated here. The modules in the aforementioned simulation device for evaluating the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structure batteries under low-velocity impact can be implemented entirely or partially through software, hardware, or a combination thereof. These modules can be embedded in or independent of the processor in a computer device, or stored in the memory of a computer device as software, so that the processor can call and execute the corresponding operations of each module.
[0085] The present invention also provides a computer-readable storage medium storing a computer program that can be used to execute the above-described... Figure 1 A simulation method for the synergistic failure of interfacial forces and electrochemical processes in carbon fiber structure batteries is provided.
[0086] This embodiment also provides a computer-readable storage medium storing a computer program thereon, which, when executed by a processor, implements the steps of the above-described method. The computer-readable storage medium can be any tangible medium that contains or stores a program, such as a floppy disk, hard disk, optical disk, magneto-optical disk, CD-ROM, magnetic tape, non-volatile memory card, etc.
[0087] This embodiment also provides a computer program product, including a computer program, which, when executed by a processor, implements the steps of the method in the specific embodiment.
Claims
1. A simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery, characterized in that, include: A three-dimensional geometric model of a carbon fiber structure battery was constructed, and an interface domain was built between each carbon fiber electrode and the electrolyte. A dynamic load simulating low-velocity impact is applied to a three-dimensional geometric model, and the interface force parameters of the interface domain under low-velocity impact load are obtained. Based on the interface stress parameters, an interface cohesive damage model based on the bilinear traction-separation law is used to determine the damage variables used to characterize the degree of interface damage in carbon fiber structure batteries; wherein, the interface cohesive damage model is used to describe the evolution of interface debonding or delamination under low-speed impact load. Based on the damage variables of carbon fiber structure batteries, an effective contact area fraction is determined to characterize the tensile or compressive state of the carbon fiber structure battery interface under low-speed impact loading. This effective contact area fraction is then introduced into the Butler-Volmer electrode kinetic equation to construct a damage coupling control equation between interfacial forces and electrochemistry in the carbon fiber structure battery. The damage variables are inversely proportional to the effective contact area fraction. This damage coupling control equation is used to simulate the dynamic process by which the evolution of interfacial debonding or delamination hinders the charge transfer reaction in the carbon fiber structure battery. The damage coupling control equation was solved by finite element simulation, and the simulation results of the interfacial force and electrochemical synergistic failure of carbon fiber structure battery under low-speed impact were obtained.
2. The simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery as described in claim 1, characterized in that, The construction of a three-dimensional geometric model for the carbon fiber structure battery, and the creation of interface domains between each carbon fiber electrode and the electrolyte, specifically includes: Obtain the characteristic dimension parameters of each part of the carbon fiber structure battery; Based on the aforementioned characteristic size parameters, a three-dimensional geometric model is constructed, comprising a carbon fiber negative electrode, a solid-liquid dual-continuous phase electrolyte, a membrane, and a carbon fiber positive electrode. An interface domain is constructed between the carbon fiber negative electrode and the solid-liquid dual-continuous phase electrolyte, and between the carbon fiber positive electrode and the solid-liquid dual-continuous phase electrolyte.
3. The simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery as described in claim 2, characterized in that, After constructing the interface domain between each carbon fiber electrode and the electrolyte, the method further includes: setting material parameters for the interface domain, specifically including: An anisotropic force-electrochemical coupling constitutive relation based on the Helmholtz free energy function is assigned to carbon fiber anode and carbon fiber cathode; wherein the Helmholtz free energy function is composed of elastic strain energy, lithium-ion mixing entropy term and lithium-ion interaction energy term; The solid-liquid bicontinuous phase electrolyte is made of resin-based material and is endowed with elastic and ion-conducting properties, as well as isotropic elastic properties for the diaphragm.
4. The simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery as described in claim 1, characterized in that, The interface force parameters of the interface domain under low-speed impact load include: interface traction force, interface strength, interface stiffness tensor, and interface separation displacement.
5. The simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery as described in claim 4, characterized in that, The damage variables used to characterize the degree of interface damage in carbon fiber structure batteries are determined based on the interface stress parameters using an interface cohesive damage model based on the bilinear traction-separation law. Specifically, these include: When the sum of the ratios of the normal and tangential components of the interfacial traction force to their respective interfacial strength components is 1, the stress parameters of the carbon fiber structure battery interface are determined as the damage initiation state of the carbon fiber structure battery interface. Under the initial damage state of the carbon fiber structure battery interface, the initiation and evolution process of debonding or delamination of the carbon fiber structure battery interface under a preset impact load is simulated by the interface cohesive damage model. During the simulation, the damage variables of the carbon fiber structure battery interface are determined based on the interface separation displacement.
6. The simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery as described in claim 1, characterized in that, The determination of the effective contact area fraction, used to characterize the tensile or compressive state of the carbon fiber structure battery interface under low-speed impact load, based on the damage variables of the carbon fiber structure battery, specifically includes: When the interface is in a stretched state, the difference between the effective contact area fraction of 1 and the damage variable is determined based on the damage variable. When the interface is in a compressed state, the effective contact area fraction is determined to be the larger of the difference between the damage variable and the preset minimum contact fraction.
7. The simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery as described in claim 1, characterized in that, The effective contact area fraction is introduced into the Butler-Volmer electrode kinetics equation to construct the damage coupling control equation between interfacial forces and electrochemistry in carbon fiber structure batteries, specifically including: Introducing the effective contact area fraction as a correction factor into the Butler-Volmer electrode kinetics equation yields the coupled control equations for the mechanical, electrochemical, and damage aspects of the carbon fiber structure battery interface, expressed as: ; In the formula, This represents the interfacial lithium-ion flux. For exchange current density, It is Faraday's constant. For the overpotential term, 、 Charge transfer coefficient; effective contact area fraction With damage variables The relationship is When the interface is completely damaged This indicates that the charge transfer reaction has terminated; The Butler-Volmer electrode kinetics equations also incorporate a mechanical contribution term into the overpotential term. This term describes the evolution of the concentration gradient stress reaction on interface damage caused by lithium ion insertion or extraction at the carbon fiber battery interface under low-velocity impact loading. The expression is as follows: ; In the formula, The electrode potential is... The potential of the electrolyte. To balance the electric potential, This represents the partial molar volume of lithium ions. For hydrostatic stress, Contribution to mechanics.
8. The simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery as described in claim 1, characterized in that, The finite element simulation solution of the damage coupling control equation specifically includes: Low-speed impact dynamic load boundary conditions are set for the three-dimensional geometric model of the carbon fiber structure battery. The boundary conditions include the mass, initial velocity and geometry of the impacting object. Set up contact pairs between the impactor and the surface of the carbon fiber structure battery, and apply fixed constraints on both sides of the carbon fiber structure battery. Considering the inertial effect, stress wave propagation, and strain rate effect experienced by the interface of a carbon fiber structure battery under low-speed impact dynamic load, the damage coupling control equation is solved by finite element method using explicit dynamic analysis, and the simulation results of the interface force and electrochemical synergistic failure of the carbon fiber structure battery under low-speed impact are output.
9. The simulation method for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery as described in claim 1, characterized in that, The simulation results of the synergistic failure of the interfacial force and electrochemical properties of the carbon fiber structure battery under low-speed impact include: damage evolution cloud map of the carbon fiber structure battery interface during low-speed impact, current density distribution map after impact, potential change curve and lithium ion concentration distribution map.
10. A simulation device for the synergistic failure of interfacial forces and electrochemical processes in a carbon fiber structure battery, characterized in that, include: The 3D model building module is used to construct the 3D geometric model of the carbon fiber structure battery and to build the interface domain between each carbon fiber electrode and the electrolyte. A dynamic load simulating low-velocity impact is applied to a three-dimensional geometric model, and the interface force parameters of the interface domain under low-velocity impact load are obtained. The interface evolution simulation module is used to determine the damage variables used to characterize the degree of interface damage of carbon fiber structure batteries based on the interface stress parameters and the interface cohesive damage model based on the bilinear traction-separation law; wherein, the interface cohesive damage model is used to describe the evolution of interface debonding or delamination under low-speed impact load. A coupling equation construction module is used to determine the effective contact area fraction, which characterizes the tensile or compressive state of the carbon fiber structure battery interface under low-speed impact loading, based on the damage variables of the carbon fiber structure battery. This effective contact area fraction is then introduced into the Butler-Volmer electrode kinetics equation to construct a damage coupling control equation between the interfacial forces and electrochemistry of the carbon fiber structure battery. The damage variables are inversely proportional to the effective contact area fraction. This damage coupling control equation is used to simulate the dynamic process by which the evolution of interfacial debonding or delamination hinders the charge transfer reaction of the carbon fiber structure battery. The interface evaluation simulation module is used to solve the damage coupling control equation using finite element simulation, and obtain simulation results of the interfacial force and electrochemical synergistic failure of carbon fiber structure batteries under low-speed impact.
